The suitability of accounting education at Saudi universities for the labor market requirements: An exploratory Study - Al-Jahdali, abrar Obaid; Abdul Rahman, Najla Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aimed to identify the suitability of accounting education at Saudi Universities for the labor market requirements, by examining the effectiveness of the application of the international Academic Accreditation standards (AACSB) for the Accounting program on the efficiency of the outputs of the accounting departments, and examining effectiveness of the developed educational Accounting curricula when applying these standards in raising the professionalism of the graduates of the accounting departments. To meet study’s objectives, the researcher adopted descriptive analysis approach to analysis a selected sample. A questionnaire was prepared and circulated among (Academic members, accounting graduates and Labor Market). The results of this research showed the correlation between the outcomes of education and the labor market requirements, and between application of international academic accreditation standards and the efficiency accounting departments’ outputs. Moreover, there is correlation between the effectiveness of developing accounting curricula when applying accreditation standards and professionalism of the graduates. The results are: The current teaching methods are able to give graduates some of expected and professional skills required. The accounting departments are interest to develop detailed plan for the program and courses. There is a need of the departments to implement joint programmers with the labor market, to qualify students to practice accounting professionally. The recommendations recommended Incorporate accounting curricula with software programs that enable students to use quantitative methods to address accounting issues, Improve the design of the curriculum to keep pace with the future development of the profession. And Strengthen the communication between accounting departments and labor market to implement programs that help qualify students to practice accounting professionally.
Keywords: accounting education; academic accreditation; labor market; Saudi Arabia